2014
DOI: 10.18632/oncotarget.1711
|View full text |Cite
|
Sign up to set email alerts
|

EGFR endocytosis is a novel therapeutic target in lung cancer with wild-type EGFR

Abstract: Oncogenic alterations of epidermal growth factor receptor (EGFR) signaling are frequently observed in lung cancer patients with worse differentiation and poor prognosis. However, the therapeutic efficacy of EGFR-tyrosine kinase inhibitors (TKIs) is currently limited in selected patients with EGFR mutations. Therefore, in this study, we investigated the potential molecular mechanism that contributes to cell viability and the response of gefitinib, one of the EGFR-TKIs, in lung cancer models with wide-type EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…We have demonstrated that the Rab25 amplicon and Rab25 expression is associated with a worsened outcome in ovarian cancer and increased the aggressiveness of a subset of breast cancer cell lines [32, 33]. Further, increased Rab25 is associated with poor patient outcome in lung [34], clear cell renal [35] and bladder [28] cancers likely through effects on metastatic pathways [36]. Mechanistically Rab25 decorated vesicles transport integrins [37, 38], PI3K [39], and EGFR [7] facilitating aggressive tumor growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the Rab25 amplicon and Rab25 expression is associated with a worsened outcome in ovarian cancer and increased the aggressiveness of a subset of breast cancer cell lines [32, 33]. Further, increased Rab25 is associated with poor patient outcome in lung [34], clear cell renal [35] and bladder [28] cancers likely through effects on metastatic pathways [36]. Mechanistically Rab25 decorated vesicles transport integrins [37, 38], PI3K [39], and EGFR [7] facilitating aggressive tumor growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells that are initially sensitive to gefitinib may eventually lose sensitivity due to the emergence of acquired resistance [44]. Alternative mechanisms are currently being explored aimed to overcome the development of gefitinib resistance in the patients of NSCLC [44, 45]. Recent studies [8, 25] show that miR-21 modulates gefitinib sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…PICALM and AP2A2 are associated with clathrin and are thus closely involved in endocytosis, one of the three main functions enriched in SDGS genes and their PPI partners (Figure ). EGFR endocytosis can be a pathway from which to find novel therapeutic targets for lung cancer with wild‐type EGFR . An abnormality in bypass signaling pathways is another of several mechanisms of EGFR resistance to TKIs, and one of those bypass pathways involves vascular endothelial growth factor (VEGF) and its receptor, VEGFR.…”
Section: Discussionmentioning
confidence: 99%